Simulation of a production line - Roslan Muhammad Amin. (2009)
This report is about a study and optimization of a new production line design using the simulation language SIMAN IV. The main focus of the project is on the examination of the line and maximizing the performance measures and these form the basis of the report. This project is based on the author's work in the application of computer simulation for a production line designed at an MNC in Singapore.